Hubs and resilience: Towards more realistic models of the interbank markets - Mattia Montagna; Thomas Lux (Kiel Institute for the World Economy (IfW), 2013)
This paper uses a toy financial system to study systemic risk in scale-free interbank networks. Networks are produced according to a fitness algorithm, combined with a representation of the balance sheets of the banks. Our generating processes for interbank networks are designed in a way to reproduce the frequently documented features of disassortative behavior, power laws in the degree distributions and power laws in the distribution of bank sizes. The results show the presence of a particular shell structure affecting the spread of an endogenous shock.
Keywords: G21; G01; E42; 330; interbank market; contagion; networks; financial stability